Biogenic nano zero valent iron (Bio-nZVI) anaerobic granules for textile dye removal. Issue 2 (April 2018) - K.V.G., Ravikumar; S., Santhosh; Sudakaran, Shruthi Vathaluru; V. Nancharaiah, Yarlagadda; P., Mrudula; Chandrasekaran, Natarajan; Mukherjee, Amitava
Highlights: nZVI granules synthesized by anaerobic granular sludge under anaerobic conditions. Methyl orange removal was studied using nZVI granules under anaerobic conditions. The Methyl orange degradation mechanism was studied. The nZVI granules applicability in real water matrixes was explored. Abstract: Zero valent iron nanoparticles (nZVI) were synthesized using anaerobic granular sludge under anaerobic conditions. UV–vis spectroscopy, X-ray diffraction, Fourier Transform Infrared spectroscopy and SEM-EDX were used for characterization of Bio-nZVI. The nZVI loaded anaerobic granular sludge (Bio-nZVI) was subsequently evaluated for removing methyl orange from aqueous solutions. Central composite design with three level factors has been employed for the determination of efficient process parameters such as methyl orange initial concentration (10–50 mg/L), weight of anaerobic granules (10–30 mg dry weight) and interaction time (90–240 min) for methyl orange removal from aqueous solution. Under the optimized conditions (weight of Bio-nZVI: 30 mg; interaction time: 240 min and initial methyl orange concentration: 10 mg/L), the removal percentage and removal capacity was found to be 99% and 168 mg/g respectively. The reduction of methyl orange by Bio-nZVI followed pseudo-second order kinetics. The granules were characterized for possible changes in the morphology and surface chemistry after methyl orange removal. The process applicability was further evaluated for removing methyl orange from ground water and lake water samples spiked with known concentrations of methyl orange.